Greece : An Update of IMF Staff's Preliminary Public Debt Sustainability Analysis. (IMF Staff Country Reports; Country Report ;, 2015)
This paper presents an update to IMF staff's Preliminary Public Debt Sustainability Analysis on Greece. Greece's public debt has become highly unsustainable. This is owing to the easing of policies during 2014, with the recent deterioration in the domestic macroeconomic and financial environment because of the closure of the banking system adding significantly to the adverse dynamics. The financing need through end-2018 is now estimated at euro 85 billion, and debt is expected to peak at close to 200 percent of GDP in the next two years, provided that there is an early agreement on a program.